Early reduction versus skin traction in the orthopaedic treatment of femoral shaft fractures in children under 6 years old - Hayek, Toni (2009)
Background Femoral shaft fractures occur very frequently in children, and their prognosis usually is good. Nonoperative treatment is the gold standard for children under 6 years because of the excellent bony union and the remodelling qualities. Purpose The aim of this study was to compare two orthopaedic therapeutic methods: skin traction versus immediate reduction. Materials and methods The study involved 35 children, divided into two groups: in group 1, treatment consisted of skin traction for 21 days followed by hip spica casting; in group 2, an immediate reduction with early hip spica casting was performed. The ranges of motion, the delay before weight bearing, the hospitalisation duration and the required amount of painkillers were recorded. We compared initial shortening, axial, sagittal and rotational alignment, and femoral length discrepancy. We calculated the injured femoral diaphysal overgrowth and correlated it to the fracture type and location and to the initial shortening. Economical variables were also studied. Results The mean overgrowth was 8.9 mm in group 1 and 8.5 mm in group 2. Three years after the trauma, length discrepancy was 4 mm in group 1 and 1 mm in group 2. Hip spica casting leads to significant reductions in weight-bearing delay, hospitalisation duration and pain. The cost of treatment with skin traction was four times higher (24,472 euros) than that of immediate reduction (6,384 euros). Discussion Our results are in accordance with the literature. The femoral overgrowth was proportional to the initial shortening. Masculine gender, an oblique fracture and injury of the lower third of the femur were associated with the greatest femoral overgrowth. During the first year of follow-up, the femoral length discrepancy hardly varied after immediate reduction (4 mm), whereas the overgrowth reached 6 mm after skin traction. Overall, immediate hip spica casting leads to significant reductions in weight-bearing delay, hospitalisation duration, complications and costs, while having similar clinical results as traction.